Antimicrobial peptides purified from hydrolysates of kanihua (Chenopodium pallidicaule Aellen) seed protein fractions - Moscoso-Mujica, Gladys (2021)
CIENCIACTIVA-CONCYTEC funded this research under contract 007-2014-FONDECYT. The professional collaboration and unconditional support of the Business administrator Pawel Moscoso-Mujica in carrying out the research are appreciated.